(untitled) (Journal of Rangpur Medical College, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) comprises a spectrum of liver diseases characterized by simple steatosis to nonalcoholic steatohepatitis (NASH), fibrosis, and cirrhosis. It is the most common cause of cryptogenic cirrhosis. NAFLD is associated with obesity, insulin resistance, hypertension, type 2 diabetes mellitus, and dyslipidemia. Objective: The study aimed to assess the changes in lipid profile and aminotransferases (ALT and AST) in Non-alcoholic fatty liver disease (NAFLD). Methods: This observational cross-sectional study was carried out in the department of Biochemistry, Mymensingh Medical College in cooperation with the Centre for Nuclear Medicine and Ultrasound, Mymensingh from January 2012 to June 2013 after the approval of the protocol. A total of 120 subjects were included through purposive sampling, among them, 60 subjects were with fatty liver disease (group-I) and another 60 were without fatty liver (group-II) with ultrasonography. The sampling method was purposive (non-random). Relevant laboratory investigations were performed by using established methods to achieve the objectives. Results: The majority of the subjects with NAFLD (33.33%) were in 51-60 years (in Group-I). Mean serum total cholesterol, triacylglycerol, LDL-cholesterol, and HDL-cholesterol were 203.33±21.83, 184.41±33.31, 126.28±18.75, and 40.17±6.32 mg/dl in group-I and 167.65±9.83, 128.77±11.65, 101.74±9.29 and 40.16±3.55 mg/dl in group-II respectively. Significant differences were found in the case of total cholesterol (p<0.001), triacylglycerol (p<0.001), and LDL-cholesterol (<0.001), but no significant difference was found in the case of HDL-cholesterol (p>0.05). Serum ALT and AST were 49.43±16.98, 45.20±13.56 U/L in group-I and 32.83±4.54, 28.68±4.31 U/L in the group- II respectively. Significant differences were found in case of ALT (p <0.001) and AST (p <0.001). Conclusion: Nonalcoholic fatty liver disease is associated with dyslipidemia and with the elevation of serum ALT and AST. J Rang Med Col. September 2022; Vol. 7, No. 2:35-39